The Optional Protocol to the UN Convention Against Torture - Murray, Rachel, Dr. (Oxford : Oxford University Press, 2011)
The Optional Protocol to the United Nations Convention Against Torture was adopted in 2002 and provides for the establishment of national preventive mechanisms to stop torture from happening. This work sets out the powers of these mechanisms their role within the international framework against torture and suggests best practices.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Torture (International law)